Biti aseksualen v heteronormativni seksualizirani družbi - Kovačič, Tanja (Etnolog. Nova vrsta (Ljubljana), 2012)
Homosexuality was removed from the list of mental diseases in 1973, but asexuality has continued to be considered a pathology to the present day. Prrsons who do no feel sexual attraction identify their sexual orientation as asexual. Asexual individuals face discrimination based on their asexuality, and their sexual identity is stigmatised. They therefore use a variety of strategies to cope with the stigma in different contexts.
Keywords: študije spolov; aseksualnost; stigma; spolnost; sexual intercourse; spolna identiteta